2009
DOI: 10.1021/jo8026593
|View full text |Cite
|
Sign up to set email alerts
|

Competing Mechanistic Channels in the Oxidation of Aldehydes by Ozone

Abstract: The reaction of ozone with aldehydes has been studied intermittently for over 100 years, but its mechanism remains uncertain. Experimental results support two reaction channels: radical abstraction of the acyl hydrogen and addition to form a five-membered ring tetroxolane. We have studied the aldehyde-ozone reaction by DFT and CCSD(T) calculations. CCSD(T)/6-311+G(d,p)//M05-2X)/6-311+G(d,p) calculations predict two competitive pathways for the oxidation of formaldehyde by ozone. Abstraction of the acyl hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 79 publications
2
21
0
Order By: Relevance
“…Comparing these seven channels, abstractions of H 20 and H 22 have lower barriers and require lower reaction heats. The energy barriers of these two H-abstraction reactions by O 3 molecules are lower than for alkanes or aldehydes (Timerghazin et al, 1999;Yang et al, 2008;Voukides et al, 2009). Moreover, DG for the H 20 and H 22 abstraction processes is less than zero, while for other processes it is larger than zero, as shown in Tables 1 and S1.…”
Section: H Abstraction By O 3 and Subsequent Reactionsmentioning
confidence: 87%
See 1 more Smart Citation
“…Comparing these seven channels, abstractions of H 20 and H 22 have lower barriers and require lower reaction heats. The energy barriers of these two H-abstraction reactions by O 3 molecules are lower than for alkanes or aldehydes (Timerghazin et al, 1999;Yang et al, 2008;Voukides et al, 2009). Moreover, DG for the H 20 and H 22 abstraction processes is less than zero, while for other processes it is larger than zero, as shown in Tables 1 and S1.…”
Section: H Abstraction By O 3 and Subsequent Reactionsmentioning
confidence: 87%
“…Studies have shown that ozonation of the CH bond in saturated hydrocarbons initiates with H abstraction by O 3 , followed by the formation of an R Å Å OOOH radical pair (Cerkovnik et al, 2002;Yang et al, 2008;Voukides et al, 2009). Within the structure of PMM, seven different kinds of hydrogen can be abstracted by O 3 , as shown in Fig.…”
Section: H Abstraction By O 3 and Subsequent Reactionsmentioning
confidence: 99%
“…Researchers have found that when cannabis leaves are treated with sodium bicarbonate, the aldehyde contents are reduced compared with untreated leaves [22]. In a reaction study of ozone and aldehydes, it was found that the slow reaction of ozone and aldehydes occurs in the atmosphere [48]. In this experiment, water was used as the reaction medium, and the long-term exposure of a high concentration of ozone had a significant impact on the aldehydes in the sample, resulting in a decline in their contents.…”
Section: Group Compoundsmentioning
confidence: 99%
“…Based on the reactional mechanism proposed by Martinez (1982) and Voukides et al (2009), carboxylic acids are potential by-products of aldehydes gas ozonation. Hence, butanoic acid was also monitored during the ozonation experiments along with BA and O 3 .…”
Section: Sift/msmentioning
confidence: 99%